An automated system for disaster management based on BRAC standard operating procedures (SOP) - Shoujanya, Rehnuma; Gonsalves, Christy Bernadatte; Harun, Mashrufa (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.